A novel and improved solar drying system appropriate for smallholder farmers. Issue 11 (1st August 2022) - Watson, Andrew G.; Aleckovic, Salko; Nallamothu, Rajeev
Abstract: Indian smallholder farmers use open sun drying to produce about 50% of the global supply of dry chili. Quality specifications in developed country markets require grading aflatoxin contaminated product, which is sold into the Indian domestic market representing a public health risk. Many improved solar drying systems have been designed but cost and complexity has prevented widespread adoption by smallholder farmers. Our objective was to develop the lowest cost, simplest solar dryer appropriate for smallholder farmers. Zero airflow period was alternated with airflow periods reducing drying time by about 50% and inactivating mycotoxigenic fungi, enteric bacteria, and browning enzymes.